An innovative software application for surveying education. Issue 3 (24th October 2011) - Dib, Hazar; Adamo‐Villani, Nicoletta
Abstract We present an innovative educational computer application for undergraduate students enrolled in a Construction Surveying Fundamentals course. The application includes an Interactive Virtual Environment for learning surveying concepts and practices, and an e‐assessment tool that measures the individual student's cognitive and practical abilities. Results of a pilot study with 31 undergraduate students and 2 faculties showed that the software was perceived as easy to use, useful, and effective at measuring the individual student's performance. © 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:551–562, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.10.1002/cae.20580